Accounting enforcement and banking regulation impact on banks’ earnings quality - Salta, Salta; Paramita, Ratna Wijayanti Daniar; Amperawati, Endang Dwi; Widyanti, Yeni; Pradianto, Mi’raj Akbar (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the significance of accounting enforcement that aims to improve the quality of earnings of banks in Indonesia, especially in the post-global financial crisis era. It explores the intersection between banking regulation, public and banking confidence, and institutional frameworks to create economic stability and transparency. Through quantitative analysis and regression models, we demonstrate that along with banking regulation, accounting enforcement is a determinant of earnings quality and serves as a response to social trust in the integrity of financial reporting. The results of this study highlight that accounting enforcement is the primary force behind earnings quality improvements, while banking regulation is an external complementary force. This study is novel as it provides insights into the banking sector in Indonesia by finding the correlation between accounting practices, regulatory enforcement, and public confidence after the crisis. This study emphasizes, from an institutional economics perspective, the introduction of increasingly severe measures for the recovery of faith in financial intermediaries. The above paper emphasizes the significance of persisting in a diversified financial stability strategy. However, it identifies a need to strengthen enforcement and establish a sound regulatory framework to improve the quality of earnings and enhance confidence in the banking system.